THU0502 EFFICACY AND SAFETY OF SECUKINUMAB TREATMENT IN JUVENILE IDIOPATHIC ARTHRITIS PATIENTS. (13th June 2020) - Kriulin, I.; Alexeeva, E.; Dvoryakovskaya, T.; Isaeva, K.; Chomakhidze, A.; Chistyakova, E.; Lomakina, O.; Denisova, R.; Mamutova, A.; Fetisova, A.; Gautier, M.; Vankova, D.; et al.
Abstract : Background: Anti-IL-17A biologic drug secukinumab (SEC) proved to be effective for treatment of psoriatic arthritis. However data about its efficacy in juvenile idiopathic arthritis (JIA) are restricted to off-label experience. Objectives: To evaluate the effectiveness and safety of SEC in JIA patients in the National Medical Research Center of Children`s health, Moscow, Russia. Methods: 25 patients started SEC therapy from 12/2017 to 11/2019 in single-center prospective study. 3 patients withdrew treatment: two patients (8%) due to AE (1 - allergy followed by MAS after first injection and 1 – leukopenia) and one patient (4%) – after 10 months of treatment due to secondary inefficacy. Among others, 14 patients which were successfully treated for 6 months or longer were included into analysis. At the baseline, information was collected on the characteristics of the onset of the disease, previous therapy and its success. Patients were monitored at least 1 time per year. At each visit, clinical and laboratory characteristics of JIA severity were assessed. Response to therapy was assessed using the ACRPedi 30/50/70/90 criteria, the C.Wallace criteria for inactive disease (WID) and clinical remission. AEs were assessed at each visit. Results: Among 14 patients received SEC for at least 6 months, 7 (50%) have enthesitis-related arthritis, one (7.1%) – persistent oligoarthritis, 4 (28.6%) – RF-negative polyarthritis, 2 (14.3%) – psoriatic arthritis. 6 patients (42.9%) were HLA-B27 positive. Median age of JIA onset was 8.8 (IQR 5:11), age at SEC initiation – 14 (9.9:16.1), disease duration before SEC start – 3.3 (2.7:5.8). 7 (50%) were biologics-naïve, 2 (14.3%) were previously treated with anti-TNF drug, 5 (35.7%) have 2 or more different biologics in anamnesis. SEC demonstrated high efficacy after the first injection resulting in JADAS-71 decreasing in all patients by median 4.3 (1.6:7.1) points and 7/7/5/2 patients (50%/50%/35.7%/14.3%) achieved ACR Pedi 30/50/70/90 response. After 6 months of treatment, WID was achieved by 7 (50%) patients, JADAS-71 decreased from baseline level 15.2 (12.7:20.5) to 0.8 (0:4.2) points, and 14/13/11/9 patients (100%/92.9%/78.6%/64.3%) achieved ACR Pedi 30/50/70/90 response. One patients who had active uveitis at SEC initiation remained with subactive uveitis; one patient with uveitis remission had not flare episodes during follow-up period. One patient (7.1%) had successfully treated evaluation of transaminases after 4-th injection. Conclusion: Secukinumab showed high effectiveness and safety in children with JIA and can be further used both as a first-line drug in JIA associated with HLA-B27, and as an alternative drug for the ineffectiveness of the standard treatment regimen with biologics. No serious adverse events were registered during follow-up period. Disclosure of Interests: Ivan Kriulin: None declared, Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Tatyana Dvoryakovskaya: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Evgeniya Chistyakova: None declared, Olga Lomakina: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Dariya Vankova: None declared, Elizaveta Krekhova: None declared, Meyri Shingarova: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared